Prevalence of Obesity and Correlated Hypertension and Hyperglycaemia Status among Participants of a Health Screening Programme in Inanam Sub-district, Kota Kinabalu, Sabah, Malaysia - Khairul Anwar Zarkasi; Nur Zuliani Ramli; Vennila Gopal; Sadia Choudhury Shimmi; Anne Lolita Miranda; Wan Salman Wan Saudi; Caroline Sunggip (2020)
Obesity is a known risk factor for non-communicable diseases, including hypertension and diabetes mellitus, with Malaysia having the highest prevalence of obesity among Southeast Asian countries. Additionally, the delivery of medical services to the rural communities remains challenging despite efforts to increase accessibilities to the healthcare facilities. Therefore, regular health screening programmes specifically aiming at these communities are necessary for early diagnosis and intervention to prevent complications while improving the patients' quality of life. A health screening programme was conducted in a sub-district of Kota Kinabalu, Sabah, Malaysia, where 50 participants were examined for general obesity based on body mass index (BMI) together with central obesity according to waist circumference (WC) and waist-to-hip ratio (WHR). Bioelectrical impedance analysis was performed to estimate body fat percentage (fat%) and body fat mass, along with the measurement of systolic blood pressure (SBP), diastolic blood pressure (DBP), and capillary blood glucose. The median age of the participants was 39.50 years. The prevalence of general obesity, central obesity based on WC and WHR, hypertension, and hyperglycaemia was 28%, 78%, 74%, 24%, and 20%, respectively. Both fat% and fat mass had positive correlations to the BMI (fat%: r = 0.656, p = 0.001; fat mass: r = 0.868, p = 0.001) and WC (fat%: r = 0.505, p = 0.001; fat mass: r = 0.761, p = 0.001). DBP had positive correlations with the BMI (r = 0.390, p = 0.005), WC (r = 0.467, p = 0.001), and WHR (r = 0.331, p = 0.019), while SBP had a positive correlation only with WC (r = 0.341, p = 0.015). Conversely, capillary blood glucose had no significant correlation with either BMI, WC, or WHR. The higher prevalence of central obesity among participants of the health screening program compared to the national level should raise concern among the healthcare providers regarding the future risk for hypertension and hyperglycaemia in this community.